2007
DOI: 10.1158/0008-5472.can-06-3388
|View full text |Cite
|
Sign up to set email alerts
|

High Number of Intraepithelial CD8+ Tumor-Infiltrating Lymphocytes Is Associated with the Absence of Lymph Node Metastases in Patients with Large Early-Stage Cervical Cancer

Abstract: In a prospective study, we have examined the tumor-specific immune response in a group of 59 patients with human papillomavirus (HPV) 16-positive (HPV16 + )-induced or HPV18 + -induced cervical cancer. Local antitumor immunity was analyzed by the enumeration of tumor-infiltrating dendritic cells and CD4 + , CD8 + , and regulatory T cells as well as by calculation of the ratio of CD8 + /CD4 + T cells and CD8 + / regulatory T cells. Systemic tumor-specific immunity was assessed by determination of the HPV E6-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
254
1
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(287 citation statements)
references
References 41 publications
19
254
1
13
Order By: Relevance
“…The proportion of CD4 1 T cells was significantly lower in tumors from patients with lymph node metastases than in those from patients without lymph node metastases, as was the reversed CD4/ CD8 ratio. Similarly, Piersma et al 31 found a significantly stronger CD8 1 T-cell tumor infiltration, a higher CD8 1 /CD4 1 T-cell ratio, and a higher CD8 1 /Tregs ratio in patients with tumors that failed to metastasize to the tumor-draining lymph node. Loddenkemper et al, 27 in a comparison study of high-grade CIN (CIN III) and cervical carcinoma with colon cancer, skin melanoma and bronchial carcinoma, revealed that HPV-derived lesions have a significantly higher number of infiltrating lymphocytes and FOXP3 1 Tregs as compared with three other common tumor types.…”
Section: Comparative Numbers Of Cd4mentioning
confidence: 80%
See 1 more Smart Citation
“…The proportion of CD4 1 T cells was significantly lower in tumors from patients with lymph node metastases than in those from patients without lymph node metastases, as was the reversed CD4/ CD8 ratio. Similarly, Piersma et al 31 found a significantly stronger CD8 1 T-cell tumor infiltration, a higher CD8 1 /CD4 1 T-cell ratio, and a higher CD8 1 /Tregs ratio in patients with tumors that failed to metastasize to the tumor-draining lymph node. Loddenkemper et al, 27 in a comparison study of high-grade CIN (CIN III) and cervical carcinoma with colon cancer, skin melanoma and bronchial carcinoma, revealed that HPV-derived lesions have a significantly higher number of infiltrating lymphocytes and FOXP3 1 Tregs as compared with three other common tumor types.…”
Section: Comparative Numbers Of Cd4mentioning
confidence: 80%
“…A significant difference was observed between the survival rates of patients with high and low CD4 1 /CD8 1 T-cell ratios (82.4% versus 44.4%, P50.029) (Figure 6). 31 observed that the presence of intratumoral CD8 1 T cells in cervical cancer was correlated with the lack of pelvic lymph node spread and was, therefore, correlated indirectly with prognosis. A high number of tumor-infiltrating CD8 1 T lymphocytes were observed as a favorable prognostic factor for survival in some studies of human cancers, including endometrial cancer, 32 ovarian cancer, 8 colorectal cancer, 33 esophageal cancer 34 and urothelial carcinoma.…”
Section: Comparative Numbers Of Cd4mentioning
confidence: 97%
“…It is expressed on cytotoxic T cells that have the capability of killing tumour cells. In a recent study by Piersma et al (2007) the presence of intratumoural CD8 þ cells in cervical cancer correlated with the lack of pelvic lymph node spread and therefore correlated indirectly with prognosis. Also in other cancer types as ovarian cancer (Sato et al, 2005), endometrial cancer (Kondratiev et al, 2004), colon cancer (Guidoboni et al, 2001) and lung cancer (Eerola et al, 2000) have intratumoural CD8 þ cells that have been correlated to improved prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…Around the same time, Diederichsen Axel et al (2003) reported that a high CD8/CD4 ratio is associated with a better prognosis in colorectal cancer. Furthermore, Piersma et al (2007)also reported that a higher CD8/ CD4 ratio is associated with the lack of tumour metastases in the draining lymph nodes of cervical cancer patients. Therefore, it is obvious that the balance of CD4 þ T cell and CD8 þ T cell is critical for prognosis of patients with cancer.…”
Section: Discussionmentioning
confidence: 96%